The Impact of Social Media Content Marketing on Consumer Purchase Behavior: A Comprehensive Literature Review - Weng, Yixin (Exploring Science Academic Conference Series, 2026)
This study presents a comprehensive literature review investigating how social media content marketing influences consumer purchase behavior through a complex sequence of psychological and social mechanisms. These mechanisms operate within contemporary digital ecosystems that are increasingly characterized by algorithmic content distribution, influencer-driven communication, and the seamless integration of social commerce features. Unlike traditional advertising models that rely heavily on persuasive interruption, modern social media content marketing emphasizes value-based communication strategies. These strategies are designed to deliver informational, experiential, and relational benefits, thereby encouraging voluntary consumer engagement and fostering long-term brand relationships. By synthesizing fragmented findings from interdisciplinary research across marketing, consumer behavior, and information systems domains, this review develops a conceptual mechanism framework in which content quality stimulates consumer engagement, engagement facilitates electronic word-of-mouth diffusion, electronic word-of-mouth strengthens consumer trust, and trust ultimately drives purchase intention and purchasing behavior. Employing literature review involves structured database search, screening procedures, and thematic synthesis. This study integrates empirical evidence across multiple platforms, industries, and cultural contexts to identify consistent patterns and theoretical inconsistencies. Findings reveal that content credibility, authenticity, and informativeness function as primary antecedents of engagement and trust formation, while peer validation, influencer credibility, and community interaction operate as amplification mechanisms that reduce perceived risk and enhance consumer confidence in brand claims. The review further identifies research gaps related to platform-specific dynamics, cross-cultural variations, and methodological limitations, providing theoretical contributions and managerial implications that support the design of trust-oriented, engagement-driven content marketing strategies in increasingly competitive and socially mediated digital marketplaces.